AirAsia Malaysia 2001 - Dixit, Mukund R.; Jena, Sanjay Kumar (London : Indian Institute of Management, Ahmedabad, 2019)
This case presents the situation faced by Tony Fernandes, Vice-President of Warner Brothers, ASEAN region, in 2001, when he had to decide whether he should be venturing into the aviation business by acquiring an existing airline or drop the idea altogether. Fernandes was interested in starting a budget airline in Malaysia on the lines of low-cost airlines in the USA and Europe. Along with two close associates, he had presented a proposal to Mahathir bin Mohammad, the Prime Minister of Malaysia, to start a low-cost airline. Mohammad rejected the proposal and suggested that Fernandes could consider buying an existing airline. Malaysia had four scheduled airlines including Malaysian Airlines (MA), the national carrier, AirAsia Sdn. Bhd (AAB) and two regional airlines, Pelangi Air and Berjaya Air. A senior officer from Diversified Resources Berhad-Heavy Industries Corporation of Malaysia (DRB-HICOM) had suggested that Fernandes might consider buying AAB and entering the aviation business in Malaysia.This case provides adequate information on the background of Fernandes and his team, the performance of AAB, the opportunities and constraints in the Malaysian air transportation industry and the profiles of leading low-cost airlines, to enable the participants to discuss the pros and cons of acquiring AAB and arrive at a decision. Conceptually it helps the participant to build the concept of entry through the acquisition mode as opposed to setting up a new company. In the larger context, it involves the participants in evaluating a strategic opportunity for a new entrant.
Originally Published InDixit, M., & Jena, S. (2019). AirAsia Malaysia 2001. IIMA/BP0430. Ahmedabad, India: Indian Institute of Management, Ahmedabad.
Description based on XML content.
Keywords: elektronické knihy; electronic books; AirAsia -- Case studies; Airlines -- Malaysia -- Case studies